2020
DOI: 10.3390/diagnostics10070450
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Idiopathic Pulmonary Fibrosis: Focus on Their Clinical and Radiological Features

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fibrotic lung disease with uncertain origins and pathogenesis; it represents the most common interstitial lung disease (ILD), associated with a pathological pattern of usual interstitial pneumonitis (UIP). This disease has a poor prognosis, having the most lethal prognosis among ILDs. In fact, the progressive fibrosis related to IPF could lead to the development of complications, such as acute exacerbation, lung cancer, infections, pneumothorax and pulmonary hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…In human medicine, HRCT is commonly used in patients with lower airway disease (17), and in addition to specifying the cause of the disease, HRCT with computed tomographic angiography (CTA) can identify comorbidities with repercussions on prognosis such as PH (18). In humans, diameter of the pulmonary trunk (PT), pulmonary trunk-to-aorta ratio (PT/Ao), and right ventricle-to-left ventricle ratio (RV/LV) are measured alone or in combination to assess the presence of PH (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, HRCT is commonly used in patients with lower airway disease (17), and in addition to specifying the cause of the disease, HRCT with computed tomographic angiography (CTA) can identify comorbidities with repercussions on prognosis such as PH (18). In humans, diameter of the pulmonary trunk (PT), pulmonary trunk-to-aorta ratio (PT/Ao), and right ventricle-to-left ventricle ratio (RV/LV) are measured alone or in combination to assess the presence of PH (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment risk stratification is especially emphasized in lung cancer patients with IPF, as the lung is vulnerable to cancer‐related therapies in this group, thus unexpectedly leading to a disastrous event. 29 Although previous studies already demonstrated that pretreatment ILA is a risk factor for pulmonary complication following cancer‐related therapies, 8 our study goes one step further and raises the need to put patients with pretreatment ILA on the same line as IPF and establish different treatment strategies.…”
Section: Discussionmentioning
confidence: 81%
“…This condition is accompanied by scarring and thickening of the tissue around and between the alveoli in lung tissue. This condition has various symptoms and complications, including shortness of breath, a dry cough, weight loss, nail clubbing, pulmonary hypertension, lung cancer, and pneumothorax [ 37 ]. During fibrosis, pro-fibrotic mediators are secreted from the activated macrophages and neutrophils and promote the accumulation of myofibroblasts that produce extracellular matrix (ECM) [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%